GE_GERICHTE C/9740/2012 vom 28. Mai 2014 - GE Cour de justice (2014)
BAIL À LOYER; EFFICACITÉ; RÉSILIATION; EXPULSION DE LOCATAIRE; SOUS-LOCATION; APPROBATION(EN GÉNÉRAL); BAILLEUR(BAIL À LOYER) | CO.257f.3